2017
DOI: 10.7717/peerj.3756
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tire leachate on the invasive mosquito Aedes albopictus and the native congener Aedes triseriatus

Abstract: Discarded vehicle tire casings are an important artificial habitat for the developmental stages of numerous vector mosquitoes. Discarded vehicle tires degrade under ultraviolet light and leach numerous soluble metals (e.g., barium, cadmium, zinc) and organic substances (e.g., benzothiazole and its derivatives [BZTs], polyaromatic hydrocarbons [PAHs]) that could affect mosquito larvae that inhabit the tire casing. This study examined the relationship between soluble zinc, a common marker of tire leachate, on mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 47 publications
1
21
0
Order By: Relevance
“…This implies that car tire TP effects can be more mild or even absent under ecologically relevant conditions than suggested in elutriate tests. 10 , 19 , 22 As the maximum Predicted Environmental Concentrations (PEC) in sediments range from 0.3 to 155 g/kg dry weight, 9 we can conclude that car tire TP pose a low risk to freshwater benthic invertebrates. This is in agreement with previous studies evaluating the effects of TRWP mixed with sediments on aquatic organisms.…”
Section: Resultsmentioning
confidence: 90%
“…This implies that car tire TP effects can be more mild or even absent under ecologically relevant conditions than suggested in elutriate tests. 10 , 19 , 22 As the maximum Predicted Environmental Concentrations (PEC) in sediments range from 0.3 to 155 g/kg dry weight, 9 we can conclude that car tire TP pose a low risk to freshwater benthic invertebrates. This is in agreement with previous studies evaluating the effects of TRWP mixed with sediments on aquatic organisms.…”
Section: Resultsmentioning
confidence: 90%
“…Wagner et al (2018) conducted a review on the toxic effects of TPs in aquatic environments and concluded that the toxicity might be due to leaching of toxic compounds such as Zn . In these toxicology tests, the test organisms were exposed to leachates after the removal of TPs; and exposure led to a significant reduction in survival, further suggesting that TP-derived compounds are responsible for the high toxicity of TPs. Moreover, TP leachates treated with ion-exchange or solid-phase extraction (SPE) columns exhibited reduced toxicity, indicating that organic compounds such as PAHs contribute to the toxicity of TPs. , Nevertheless, the mechanisms behind TP-inducted effects on the biota need further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Another physiological adaptation of Ae. albopictus larvae that facilitates their survival in tyres is their superior tolerance to contaminants in tyre leachate compared with other mosquito species [57]. Furthermore, Ae.…”
Section: Discussionmentioning
confidence: 99%